Implementing Entrepreneurial Ideas: The Case for Intention - Bird, Barbara (Academy of Management Review, 1988)
Although entrepreneurial ideas begin with inspiration, intention and attention are needed to realize the ideas. This analysis focuses on the conscious and intended act of creating a firm, but less on the action than the psychological precursors to that act. Entrepreneurial intentions are directed at creating a new venture or new values in existing ones. Studying intention directs theory toward the complex relationships among entrepreneurial ideas and their consequences. Intention is structured by rational, analytic, and causal processes, and is framed and structured by intuitive, holistic, and contextual thinking. A behavioral, not an institutional, model is presented that guides attention to how entrepreneurs create, sustain, and transform organizations. The model thus distinguishes entrepreneurship from strategic management. The model is based on interviews with 20 entrepreneurs using a discovery-oriented inquiry Five antecedent and three intrapsychic processes are identified. Intention sustains temporal tension and strategic focus; developing an intentional posture requires alignment to a single purpose and direction, and attunement to the entrepreneurial environment. Entrepreneurial intentions impact organizational direction, survival, growth, and form. The model allows deeper insight into the creative process of venture development; and it allows entrepreneurship to be studied consistent with theories of leadership, organizational development, and organizational theory. The model moves research beyond description and statistical analysis. An entrepreneur's actions create organizational theories that may be discovered and analyzed. (TNM)